A simple method of plant sectioning using the agarose embedding technique for screening intracellular green fluorescent protein - Nisa Ihsani; Fenny Martha Dwivany; Sony Suhandono (Universitas Gadjah Mada, 2023)
It is difficult to observe plant tissue sections transformed using the agroinfiltration method under a fluorescent microscope. This is due to the softness of the post‐transformation plant. This research was conducted to optimize the sectioning of tobacco stems transformed through the agarose embedding technique. Optimization was conducted at various agarose concentrations: 2%, 4%, and 6%, followed by five minutes of incubation at various temperatures: –80 °C, 4 °C, and 25 °C. The stems were then cut using a scalpel and examined under a fluorescence microscope. The results showed that the embedding method using 6% agarose was more effective at producing a tobacco stem section than 2% or 4% agarose. Meanwhile, incubation at 25 °C was better suited to the transformed tobacco stems than at 4 °C or –80 °C. Green Fluorescent Protein (GFP) could be determined under a fluorescent microscope when using the optimum method. Thus, the optimum method for creating sections of transformed tobacco stems by embedding was to use 6% agarose followed by incubation at 25 °C for 5 min. The optimum result can be applied to obtain a slight section of tobacco stem in order to observe a recombinant protein or other anatomical structures.